Heracles and epilepsy: the sacred disease - Eduardo ORREGO-GONZÁLEZ; Ana PERALTA-GARCÍA; Leonardo PALACIOS-SÁNCHEZ (Arquivos de Neuro-Psiquiatria)
ABSTRACT Epilepsy is one of the most dreaded and terrifying human afflictions. One of the many names it has received was Sacred Disease, during Greek times. Heracles served as a source of the divine connotation that epilepsy received in ancient times, as he was one of the most important demigods in Greek mythology. However, several authors have attributed Heracles’ actions to a seizure, including Hippocrates, who described the sacred disease on his “Corpus Hippocraticum.” This paper reviewed some of the publications on the myth and content of the text of Hippocrates, in relation to the current knowledge of the disease.